2017
DOI: 10.1007/s00011-017-1082-y
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic involvement in etiopathogenesis and implications in treatment of systemic lupus erythematous

Abstract: Accumulating evidence disclosed that epigenetic dysregulations are engaged in SLE pathogenesis and may be exerted as biomarkers to diagnose and as tools to treat these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 141 publications
0
12
0
Order By: Relevance
“…Therefore, they are implicated in the formation of cell‐ and tissue‐specific phenotypes. Although the epigenetic modifications are highly stable, they can be modified by environmental factors and thereby act as a vital mechanism for cell survival and adaptation to the new condition or disease . Epigenetic mechanisms are theoretically involved in three important aspects of RA: contribution to disease etiology, involvement in the mechanisms of the disease development, and act as robust biomarkers of disease progression and activity .…”
Section: Involvement Of Epigenetics In Ra Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they are implicated in the formation of cell‐ and tissue‐specific phenotypes. Although the epigenetic modifications are highly stable, they can be modified by environmental factors and thereby act as a vital mechanism for cell survival and adaptation to the new condition or disease . Epigenetic mechanisms are theoretically involved in three important aspects of RA: contribution to disease etiology, involvement in the mechanisms of the disease development, and act as robust biomarkers of disease progression and activity .…”
Section: Involvement Of Epigenetics In Ra Pathogenesismentioning
confidence: 99%
“…Although the epigenetic modifications are highly stable, they can be modified by environmental factors and thereby act as a vital mechanism for cell survival and adaptation to the new condition or disease. 15,16 Epigenetic mechanisms are theoretically involved in three important aspects of RA: contribution to disease etiology, involvement in the mechanisms of the disease development, and act as robust biomarkers of disease progression and activity. 17 Surprisingly, studies on monozygotic and dizygotic twins have showed that the role of epigenetics is more significant than that of genetics with regard to RA susceptibility.…”
Section: Involvement Of Epigenetics In Ra Pathogenesismentioning
confidence: 99%
“…DNA methylation involves in many cellular phenomena such as X-chromosome inactivation, transposable retro element activities, cell differentiation, cell reprogramming, cell death, cell survival, parental gene imprinting, immune system activities and allelic exclusion of immunoglobulin genes [12,13]. DNA methylation abnormalities are linked with different diseases such as cancer, autoimmune diseases and atherosclerosis [14][15][16][17][18][19]. Investigations on DNA methylation in patients with atherosclerosis documented that there is a unique profile of DNA methylation in this disease, and emphasize on the different pathways and genes which are implicated in the disease [20].…”
Section: Introductionmentioning
confidence: 99%
“…There are several issues which need to be addressed. In case of DNA methylation, it is not completely clear that DNA methylation abnormalities, which are reported through different studies [25,[33][34][35][36][37], are actually consequence of the disease or could be considered as a disease causes. Since the DNA methylation could be affected by disease stage and chronic inflammatory situation of disease, it seems that these abnormalities are a disease consequence rather than the disease cause.…”
Section: Discussionmentioning
confidence: 99%